"Like Being Shot in the Face" or "I'm Glad I'm Out": Journalists' Experiences of Job Loss in the Australian Media Industry 2012–2014. (2nd January 2020) - Ricketson, Matthew; Dodd, Andrew; Zion, Lawrie; Winarnita, Monika
ABSTRACT: The Australian news media industry has recently experienced a dramatic contraction, resulting in the loss of an estimated 3000 journalism positions since 2011. But what does the process of being laid off (more commonly understood as "redundancy" in Australia) actually mean for those affected? Drawing on a survey of more than 200 journalists who left what were mostly long-term jobs in large newsrooms between 2012 and 2014, this paper examines how respondents conceptualised their redundancy experiences in response to an open-ended question that was part of a 2014 survey. As well as assessing the often complex and sometimes visceral responses in terms of whether they were positive, mixed or negative, the paper discusses a range of themes to emerge, and notes discrepancies that relate to whether the redundancies were voluntary or forced, and by age and gender, and to some extent, current work status. It also finds that while overall the responses to redundancy skew more negative than positive, an substantial majority of those surveyed believe their well-being has improved since leaving their jobs.